A preliminary study of stakeholders’ opinions and perceptions of elephants and elephant management in Botswana - Tempe Adams; Michael Chase; Anna Attard; Keith Leggett (Pachyderm)
Botswana has been lauded by the international conservation community for maintaining the largest population of African elephants on the continent. However, given the size of the elephant population and increasing human population in Botswana, elephants and people are forced at times to live in close proximity to each other, making human–elephant conflict difficult to avoid. It is widely acknowledged that the management of protected areas and wildlife is often a complicated and contentious issue, which requires participation by all stakeholders. This preliminary study aims to determine stakeholders’ opinions and perceptions of elephants and elephant management in Botswana. Questionnaires were distributed nationwide and were completed on a voluntary basis. The majority of those who responded, valued elephants for intrinsic reasons, such as their being part of the environment; however, there were concerns over the lack of management and how best to manage the population in the future. These concerns stemmed in part from the perceived lack of communication among stakeholders. There was a significant difference in opinion between those that lived inside and outside of the elephant range. The study provides an insight into stakeholders’ opinions and perceptions of elephant management in Botswana, providing inputs for an improved management strategy, aimed at reducing the incidence and impact of human–elephant conflict in Botswana.